2018
DOI: 10.1104/pp.18.00922
|View full text |Cite
|
Sign up to set email alerts
|

Elucidation of the Amygdalin Pathway Reveals the Metabolic Basis of Bitter and Sweet Almonds (Prunus dulcis)

Abstract: Almond (Prunus dulcis) is the principal Prunus species in which the consumed and thus commercially important part of the fruit is the kernel. As a result of continued selection, the vast majority of almonds have a nonbitter kernel. However, in the field, there are trees carrying bitter kernels, which are toxic to humans and, consequently, need to be removed. The toxicity of bitter almonds is caused by the accumulation of the cyanogenic diglucoside amygdalin, which releases toxic hydrogen cyanide upon hydrolysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
68
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(77 citation statements)
references
References 83 publications
3
68
0
1
Order By: Relevance
“…DDBJ/EMBL/GenBank accession numbers for UGT94AB2, UGT94AA2, and UGT94AG1 are LC484012, LC484014, and LC484013, respectively. The regio-selectivity of GGTs used in the analysis was described in the following studies: Brugliera et al (1994), Kroon et al (1994), Frydman et al (2004 (2014,2016), Di et al (2015), Ohgami et al (2015), Casas et al (2016), and Thodberg et al (2018).…”
Section: Phylogenetic Analysismentioning
confidence: 99%
“…DDBJ/EMBL/GenBank accession numbers for UGT94AB2, UGT94AA2, and UGT94AG1 are LC484012, LC484014, and LC484013, respectively. The regio-selectivity of GGTs used in the analysis was described in the following studies: Brugliera et al (1994), Kroon et al (1994), Frydman et al (2004 (2014,2016), Di et al (2015), Ohgami et al (2015), Casas et al (2016), and Thodberg et al (2018).…”
Section: Phylogenetic Analysismentioning
confidence: 99%
“…Our results suggest that TEs could be responsible for some of the genomic changes at the origin of the agronomic traits that distinguish peach from almond, such as mesocarp development and bitterness of the kernel. For one of them, sweet vs. bitter kernel, essential for the domestication of the almond, we show here that the sweet almond phenotype correlates with TE insertions surrounding gene CYP71AN24, involved in the synthesis of one of the key enzymes of the amygdalin pathway (cytochrome P450), and that could be responsible for the lower expression of this gene in the seed tegument of sweet almonds (Thodberg et al 2018).…”
Section: Discussionmentioning
confidence: 78%
“…It has been recently shown that the sweet almond phenotype is due to the reduced expression of the genes encoding two cytochrome P450 enzymes catalyzing the first steps of the amygdalin biosynthesis in sweet almond varieties as compared with bitter almond varieties (Thodberg et al 2018). It has also been shown that this reduced expression is not related with differences in the gene sequence, which points to a difference in the regulation of the expression of those genes (Thodberg et al 2018). We have compared these two almond genes with their homologs in peach, sweet cherry and P. mume and found that they are highly conserved (not shown).…”
Section: Transposon-induced Variability In Peach and Almond Traitsmentioning
confidence: 99%
“…5). Interestingly, PdUGT94AF1 and PdUGT94AF2 derived from Prunus dulcis involved in the formation 1,6-β-D-glucosidic linkage of Prunasin [24] were clustered in group A but had a long genetic distance between them and SrUGTs of this group, implying that the SrUGTs in this group may have no related specificity. Due to the lack of other glycosyltransferases capable of forming 1,6-glucosidic bonds, this tree cannot predict the glycosyltransferases involved in the synthesis of steviol glycosides containing 1,6-glucosidic bonds (such as Reb L).…”
Section: Content Of Glucosides In Samplesmentioning
confidence: 99%